2020
DOI: 10.1002/adma.202005074
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Processed All‐Ceramic Plasmonic Metamaterials for Efficient Solar–Thermal Conversion over 100–727 °C

Abstract:  ε 100 C of 4-10%, as well as thermal stability below 500 °C, [9,10,14-17] which can hardly satisfy the requirements of Low-cost and large-area solar-thermal absorbers with superior spectral selectivity and excellent thermal stability are vital for efficient and large-scale solar-thermal conversion applications, such as space heating, desalination, ice mitigation, photothermal catalysis, and concentrating solar power. Few state-of-the-art selective absorbers are qualified for both low-(<200 °C) and high-tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
88
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 48 publications
(131 reference statements)
1
88
0
1
Order By: Relevance
“…3a. The metamaterial absorber only offers a low of 45%, much lower than the values (~95%) on dense substrates 3 . In contrast, the intrinsic Ti 3 C 2 T x sustained its high of 85% and low of 25% even on highly porous membranes (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…3a. The metamaterial absorber only offers a low of 45%, much lower than the values (~95%) on dense substrates 3 . In contrast, the intrinsic Ti 3 C 2 T x sustained its high of 85% and low of 25% even on highly porous membranes (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Porous structures are indispensable components to a lot of solar-thermal applications, such as steam generation 1 , seawater desalination 39 , and smart textiles 45 . However, current high-performance selective solar absorbers are usually realized by constructing arti cial metamaterials/metasurfaces in nanoscale (multilayer nano lms or nanophotonic structures) on dense at substrates [2][3][4]24,26 , which will lose their effectiveness when coated on porous substrates owing to the break of resonant conditions. For instance, we coated a previously reported high-performance metamaterial absorber (Ag lm/TiN nanoparticles/SiO 2 ) on a highly porous Nylon 66 membrane shown in the inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Landy et al first experimentally demonstrated metamaterial absorbers (MMA) in 2008 [ 1 ], MMA has spurred the interest of many researchers due to its extensive application value, e.g., solar–thermal conversion [ 2 , 3 , 4 ], photovoltaic [ 5 ], plasmonic sensors [ 6 , 7 , 8 ], imaging [ 9 , 10 ], stray light elimination [ 11 ], thermal emitter [ 12 , 13 , 14 , 15 ], photodetectors [ 16 ], and so on. In recent years, various light-matter interaction mechanisms are implemented to achieve strong light absorption, such as surface plasmon polariton [ 17 , 18 ], LSPP [ 19 ], magnetic polarization [ 20 ], and Fabry–Pérot cavity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%